2013
DOI: 10.1371/journal.pone.0072493
|View full text |Cite
|
Sign up to set email alerts
|

Major Clades of Australasian Rutoideae (Rutaceae) Based on rbcL and atpB Sequences

Abstract: BackgroundRutaceae subfamily Rutoideae (46 genera, c. 660 species) is diverse in both rainforests and sclerophyll vegetation of Australasia. Australia and New Caledonia are centres of endemism with a number of genera and species distributed disjunctly between the two regions. Our aim was to generate a high-level molecular phylogeny for the Australasian Rutoideae and identify major clades as a framework for assessing morphological and biogeographic patterns and taxonomy.Methodology/Principal FindingsPhylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 107 publications
7
66
0
Order By: Relevance
“…Acronychia belongs to a clade of mainly Australasian rain forest genera in the citrus family, Rutaceae [1, 2]. The 49 accepted species in the genus may be shrubs or trees up to 30 m tall [3, 4, 5] with leaves simple or trifoliolate (both character states may occur within a single species), flowers tetramerous with eight stamens, and the gynoecium developing into a syncarpous (sometimes only at base) and drupaceous fruit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acronychia belongs to a clade of mainly Australasian rain forest genera in the citrus family, Rutaceae [1, 2]. The 49 accepted species in the genus may be shrubs or trees up to 30 m tall [3, 4, 5] with leaves simple or trifoliolate (both character states may occur within a single species), flowers tetramerous with eight stamens, and the gynoecium developing into a syncarpous (sometimes only at base) and drupaceous fruit.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Euodia and Melicope , a group of about 30 genera mainly from Asia and Australia, the so-called Euodia -alliance, are possible close relatives of Acronychia [31]. Most of these genera have been sampled in recent molecular analyses [1, 2], which showed that the Euodia -alliance is not monophyletic.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this analysis six species of Zieria form a strongly supported clade with Neobrynesia (BS 94%). The monophyly of Zieria is also suggest by Bayly et al (2013) and Appelhans et al (2014). Bayly et al (2013) using only rbcL and atpB also included Zieria chevalieri from New Caledonian, the only disjunct species within Zieria to support not only the monophyly of Zieria but also the outgroup relationship with Neobrynesia .…”
Section: Discussionmentioning
confidence: 90%
“…A subfamilial phylogenetic analysis was completed for Rutaceae by Chase et al (1999), Groppo et al (2008, 2012), Poon et al (2007), Bayly et al (2013), and Morton and Telmer (2014), using evidence from rbcL and atpB , rps16 and trnL-trnF and trnL-F , xdh , and ITS sequence variation. All of the above authors, except for Bayly et al (2013), did not include taxa from either Zieria or Neobyrnesia (sister genus to Zieria ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation